Aqueous coating composition, aqueous pole piece, and aqueous battery

By using a water-based coating composition containing a specific structure polymer in an aqueous battery, a three-dimensional mesh crosslinking structure is formed, which solves the problem of insufficient water resistance and adhesion of the water-based electrode sheet, and improves the safety and circulation performance of the battery .

CN119490779APending Publication Date: 2025-02-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311021430.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In existing water-based batteries, the water-based pole plates have insufficient water resistance and adhesion, resulting in poor battery safety and circulation performance.

Method used

Using a water-based coating composition containing a polymer of a specific structure, the adhesion and water resistance of the water-based electrode sheet are improved by forming a three-dimensional mesh crosslinking structure.

Benefits of technology

It significantly improves the water resistance and adhesion of the water-based electrode sheet, and enhances the safety and circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490779A_ABST
    Figure CN119490779A_ABST
Patent Text Reader

Abstract

The invention provides a water-based coating composition, a water-based pole piece and a water-based battery, the water-based coating composition comprises a water-based binder and a solvent, the water-based binder comprises a first polymer, the first polymer comprises a structural unit represented by a formula (1) and a structural unit represented by a formula (2), in the formula (1), in the formula (2), in the formula (1), in the formula (2), in the formula (2), in the formula (2), in the formula (2), in the formula (2), the structural unit is in the formula (1), R1, R2 and R3 are independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano or nitro, L is a connecting bond or C1-10 alkylene, in the formula (2), R4, R5 and R6 are independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano or nitro, and n is 2-12. The water-based coating composition can improve the binding power and water resistance of the water-based coating, thereby improving the safety performance and cycle performance of the water-based battery. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an aqueous coating composition, an aqueous electrode and an aqueous battery. Background Art

[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As secondary batteries have made great progress, higher requirements have been put forward for their performance.

[0003] At present, aqueous batteries have attracted widespread attention due to their environmentally friendly and pollution-free characteristics. Aqueous batteries have high requirements for the water resistance of aqueous electrodes. Therefore, how to make aqueous electrodes have excellent water resistance and improve the safety and cyclability of aqueous batteries has become an urgent problem to be solved in this field. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide an aqueous coating composition, an aqueous electrode and an aqueous battery, thereby improving the adhesion and water resistance of the aqueous electrode, reducing the risk of the aqueous coating falling off, and further improving the safety performance and cycle performance of the aqueous battery.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a water-based coating composition, characterized in that it contains an aqueous binder and a solvent, the aqueous binder contains a first polymer, and the first polymer contains a structural unit shown in formula (1) and a structural unit shown in formula (2).

[0006]

[0007] In formula (1), R1, R2, and R3 are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro, and L is a connecting bond or a C1-10 alkylene group.

[0008]

[0009] In formula (2), R4, R5, and R6 are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro, and n=2 to 12.

[0010] The carboxyl group in the structural unit represented by formula (1) and the hydroxyl group in the structural unit represented by formula (2) in the aqueous coating composition of the present application can form hydrogen bonds and / or cross-linked structures, thereby improving its adhesion in the aqueous electrode, enabling the aqueous electrode to obtain excellent water resistance, reducing the risk of demolding, and improving the safety and cyclability of the battery.

[0011] In any embodiment, in formula (1), R1, R2, and R3 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano, L is a linking bond or a C3-4 alkylene group, and in formula (2), R4, R5, and R6 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano, and n=3 to 6. By making the structural units represented by formula (1) and formula (2) contain the above functional groups, the adhesion between the aqueous coating and the current collector can be improved, and as the battery is used for a longer time, the improvement of the adhesion is conducive to further improving the cycle performance.

[0012] In any embodiment, in the first polymer, the mass proportion of the structural unit represented by the formula (1) is 10% to 75%, and the mass proportion of the structural unit represented by the formula (2) is 5% to 40%. By making the content of each structural unit within the above range, a high-density cross-linked network structure can be formed.

[0013] In any embodiment, the first polymer further comprises a structural unit represented by formula (3) and / or a structural unit represented by formula (4),

[0014]

[0015] In formula (3), R7, R8, and R9 are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro.

[0016] R 10 is a rigid group, optionally a cyano group, an acylamino group or an aryl group, optionally a cyano group,

[0017]

[0018] In formula (4), R 11 , R 12 , R 13 Each is independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxy, cyano or nitro, and m=2-12.

[0019] The structural unit shown in formula (3) is a hard segment that can provide strength to the material, and the structural unit shown in formula (4) is a soft segment that can provide flexibility to the material. This can enhance the wetting and spreading of the water-based coating on the substrate, especially the oil-containing substrate (for example, oil-containing aluminum foil), which is beneficial to improving the adhesion and water resistance.

[0020] In any embodiment, in the first polymer, the mass proportion of the structural unit represented by formula (3) is 5% to 40%. In any embodiment, in the first polymer, the mass proportion of the structural unit represented by formula (4) is 10% to 75%. Thus, the water-based coating can have appropriate hardness and flexibility, which is beneficial to improving the adhesion and water resistance of the water-based coating.

[0021] In any embodiment, in the first polymer, the mass proportion of the structural unit represented by the formula (1) is 30% to 55%, the mass proportion of the structural unit represented by the formula (2) is 5% to 15%, the mass proportion of the structural unit represented by the formula (3) is 10% to 20%, and the mass proportion of the structural unit represented by the formula (4) is 30% to 55%. By making each structural unit within the above content range, it is beneficial to improve the bonding force and water resistance.

[0022] In any embodiment, the number average molecular weight of the first polymer is 200,000 to 1,000,000, and optionally 300,000 to 600,000. By making the number average molecular weight within the above range, the binder molecular chains can be partially entangled inside the water-based coating, which is conducive to the formation of a three-dimensional network structure in the water-based coating and improves the bonding force. At the same time, by making the number average molecular weight within the above range, the above entanglement can be controlled within a moderate range, thereby obtaining excellent flexibility.

[0023] In any embodiment, the aqueous binder further comprises a second polymer, which is different from the first polymer and comprises a group capable of reacting with the first polymer, and the group can form a hydrogen bond and / or a cross-linked structure with the first polymer. By further comprising a second polymer, which forms a hydrogen bond and / or a cross-linked structure with the first polymer, a high-density three-dimensional network cross-linked structure can be formed, thereby further improving the bonding force and the water resistance of the aqueous coating.

[0024] In any embodiment, the second polymer comprises a flexible group, and the flexible group is a group comprising an ester bond or a group comprising an ether bond. By making the polymer comprise a flexible group, the flexibility of the binder can be increased, the brittleness of the coating can be improved, and the water resistance of the water-based coating can be improved.

[0025] In any embodiment, the second polymer comprises a structural unit represented by formula (5), a structural unit represented by formula (6), and a structural unit represented by formula (7).

[0026]

[0027] In formula (5), R'1, R'2, and R'3 are the same as or different from R1, R2, and R3, respectively, and are independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro; L' is the same as or different from L, and is a connecting bond or a C1-10 alkylene group.

[0028]

[0029] In formula (6), R'4, R'5, and R'6 are the same as or different from R4, R5, and R6, respectively, and are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro, n' is the same as or different from n, and n'=2 to 12.

[0030]

[0031] In formula (7), R' 11 , R' 12 , R' 13 With R 11 , R 12 , R 13 are the same or different, and are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxy, cyano or nitro, m' is the same as or different from m, and m'=2-12.

[0032] The carboxyl group of the structural unit represented by formula (5) in the above-mentioned second polymer and / or the hydroxyl group of the structural unit represented by formula (6) can form hydrogen bonds and / or cross-linking structures with the carboxyl group of the structural unit represented by formula (1) and / or the hydroxyl group of the structural unit represented by formula (2) in the above-mentioned first polymer, forming a high-density three-dimensional network cross-linking structure, which is beneficial to improving the adhesion and water resistance of the water-based coating.

[0033] In any embodiment, in formula (5), R'1, R'2, and R'3 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano, L' is a connecting bond or a C3-4 alkylene group, in formula (6), R'4, R'5, and R'6 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano, n'=3-6, in formula (7), R' 11 , R' 12 , R' 13Each is independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl or cyano, and m' is 3 to 6. By optimizing the structure of the structural unit, it is beneficial to form a high-density three-dimensional network system, which is beneficial to improve the bonding force and water resistance.

[0034] In any embodiment, in the second polymer, the mass proportion of the structural unit represented by formula (5) is 10% to 60%, the mass proportion of the structural unit represented by formula (6) is 5% to 20%, and the mass proportion of the structural unit represented by formula (7) is 20% to 60%. By making the content of each structural unit within the above range, it is beneficial to form a high-density three-dimensional network cross-linking system, which is beneficial to further improve the bonding force and water resistance.

[0035] In any embodiment, the number average molecular weight of the second polymer is 200,000 to 1.2 million, and optionally 250,000 to 600,000. By making the number average molecular weight within the above range, the binder molecular chains can be partially entangled inside the water-based coating, which is conducive to the formation of a three-dimensional network structure in the water-based coating and improves the bonding force. At the same time, by making the number average molecular weight within the above range, the above entanglement can be controlled within a moderate range, thereby obtaining excellent flexibility.

[0036] In any embodiment, the structural unit of formula (2) and the structural unit of formula (6) are By making the above structural unit into this specific structure, the bonding force of the adhesive in the water-based electrode is greatly improved, and the water resistance of the water-based electrode is improved.

[0037] In any embodiment, the mass ratio of the first polymer to the second polymer is 9: 1 to 1: 9, and optionally, 4: 1 to 1: 4. By making the mass ratio of the first polymer to the second polymer within the above range, hydrogen bonds can be formed at a high density, which is conducive to forming a high-density three-dimensional network system and further improving water resistance.

[0038] In any embodiment, the solvent is water. By using water as a solvent, the cost is low and the environment is pollution-free. In any embodiment, the composition further comprises an insulating material and / or a dispersant. Optionally, the insulating material is a ceramic material. Optionally, the ceramic material is boehmite powder. Optionally, the dispersant is a polyacrylamide-based dispersant. This is conducive to improving the insulation and the safety performance of the battery.

[0039] The second aspect of the present application also provides an aqueous electrode, characterized in that it includes an aqueous coating, wherein the aqueous coating is formed by the aqueous coating composition of the first aspect of the present application, and has a three-dimensional network cross-linked structure. By including a three-dimensional network cross-linked structure in the aqueous coating, the adhesion and water resistance of the aqueous coating are improved, thereby improving the cycle performance and safety performance of the battery.

[0040] In any embodiment, the water-based coating contains 10% to 30% by mass of an aqueous binder relative to the total mass of the water-based coating, and optionally 15% to 25% by mass. By making the content of the binder within the above range, the bonding force of the water-based coating can be increased, the water resistance can be improved, and the content of the insulating material can be increased, thereby improving the insulating effect.

[0041] In any embodiment, the aqueous coating contains 65% to 80% by mass of insulating material relative to the total mass of the aqueous coating, and 0.2% to 1.0% by mass of dispersant relative to the total mass of the aqueous coating, thereby improving the insulation and the safety performance of the battery.

[0042] In any embodiment, the contact angle between the water-based coating and water is less than or equal to 90°, and can be optionally 40° to 80°. As a result, the wettability of the water-based coating in the water-based electrode is good, the coating is spread more fully on the substrate, and the contact area is increased, which is conducive to improving the adhesion of the water-based coating to the substrate surface and reducing the risk of falling off.

[0043] In any embodiment, the peel strength of the aqueous coating on the aqueous electrode is greater than or equal to 10 N / m, optionally greater than or equal to 17 N / m, and the peel strength is obtained by performing a 180° peel test based on the national standard GB / T 41511-2022.

[0044] In any embodiment, the aqueous electrode sheet is an aqueous positive electrode sheet or an aqueous negative electrode sheet.

[0045] The third aspect of the present application also provides an aqueous battery, which includes the aqueous electrode of the second aspect of the present application. Therefore, the aqueous battery of the present application has excellent safety performance and cycle performance.

[0046] The fourth aspect of the present application also provides an electrical device, which includes the aqueous battery of the third aspect of the present application.

[0047] Effects of the Invention

[0048] The aqueous coating composition of the present application includes a polymer with a specific structure as an aqueous binder, forming a three-dimensional network cross-linked structure in the aqueous coating, thereby improving the adhesion of the aqueous coating in the electrode, thereby improving the water resistance of the coating. In addition, the polymer contains a flexible structural unit with an ester structure, which can increase the flexibility of the coating and help to further improve the water resistance of the coating. The aqueous electrode of the present application includes a coating with high adhesion and high water resistance, thereby realizing the application of aqueous electrode technology and improving the safety performance and cycle performance of aqueous batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a partial schematic cross-sectional view of a pole piece according to some embodiments of the present application.

[0050] Figure 2 This is an infrared spectrum obtained by performing infrared testing on the first polymer 1-20 obtained in the preparation example of this application.

[0051] Figure 3 This is an infrared spectrum obtained by performing infrared testing on the aqueous coating of the positive electrode plate after disassembling the battery prepared in Example 24 of the present application.

[0052] Description of Reference Numerals

[0053] 1-current collector; 11-conductive layer; 12-insulating layer; 13-substrate; 2-active material layer. DETAILED DESCRIPTION

[0054] The following is a detailed description of the embodiments of the aqueous coating composition, aqueous electrode, aqueous battery and electrical device of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0055] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0056] Unless otherwise indicated, the following terms used in the specification and claims have the following meanings:

[0057] "Halogen" refers to fluorine, chlorine, bromine or iodine, optionally fluorine or chlorine.

[0058] "Alkyl" refers to a saturated aliphatic hydrocarbon group, including straight and branched groups of 1 to 20 carbon atoms. Optionally, it is a medium-sized alkyl group containing 1 to 10 carbon atoms, such as methyl, ethyl, propyl, 2-propyl, n-butyl, isobutyl, tert-butyl, amyl, etc. Furthermore, it is optionally a low alkyl group containing 1 to 4 carbon atoms, such as methyl, ethyl, propyl, 2-propyl, n-butyl, isobutyl or tert-butyl, etc. The alkyl group can be substituted or unsubstituted. When substituted, the group is optionally halogen, hydroxyl, lower alkoxy, aryl, aryloxy, heteroaryl, heterocycloalkyl.

[0059] The "hydroxyalkyl group" refers to a group in which a hydrogen atom in the above-mentioned alkyl group is substituted with a hydroxy group.

[0060] "Cycloalkyl" refers to a 3-8-membered all-carbon monocyclic ring, an all-carbon 5-membered / 6-membered or 6-membered / 6-membered fused ring, or a polycyclic fused ring ("fused ring" means that each ring in the system shares a pair of adjacent carbon atoms with other rings in the system) group, wherein one or more rings may contain one or more double bonds, but no ring has a completely conjugated π electron system. Examples of cycloalkyl include cyclopropyl, cyclobutyl, cyclopentyl, cyclopentene, cyclohexane, cyclohexadiene, adamantane, cycloheptane, cycloheptatriene, etc. Cycloalkyl may be substituted or unsubstituted. When substituted, it may be one or more substituents, which are independently selected from lower alkyl, trihaloalkyl, halogen, hydroxyl, lower alkoxy, aryl, aryloxy, 6-membered heteroaryl, 5-membered heteroaryl, or 5 or 6-membered heterocycloalkyl, sulfhydryl, (lower alkyl) sulfenyl, cyano, nitro, carboxyl, ester.

[0061] "Alkoxy" refers to -O-(alkyl) and -O-(unsubstituted cycloalkyl). Here, alkyl and cycloalkyl are defined as above. Representative examples include, but are not limited to, methoxy, ethoxy, propoxy, butoxy, cyclopropyloxy, cyclobutyloxy, cyclopentyloxy, cyclohexyloxy, and the like.

[0062] "Alkenyl" refers to an alkyl group as defined above consisting of at least two carbon atoms and at least one carbon-carbon double bond. Representative examples include, but are not limited to, vinyl, 1-propenyl, 2-propenyl, 1-, 2- or 3-butenyl, and the like.

[0063] "Alkynyl" refers to an alkyl group as defined above consisting of at least two carbon atoms and at least one carbon-carbon triple bond. Representative examples include, but are not limited to, ethynyl, 1-propynyl, 2-propynyl, 1-, 2- or 3-butynyl, and the like.

[0064] "Heterocycloalkyl" refers to a monocyclic or condensed ring group, in which there are 5 to 9 ring atoms, one or two of which are selected from nitrogen, oxygen or sulfur, and the remaining ring atoms are carbon. These rings may also have one or more double bonds, but these rings do not have a completely conjugated π electron system. Unsubstituted heterocycloalkyl includes, but is not limited to, pyrrolidinyl, piperidino, morpholinyl, thiomorpholinyl, homopiperazinyl, etc., and heterocycloalkyl may be substituted or unsubstituted. When substituted, the substituent is preferably one or more substituents selected from the following optionally substituted: halogen, trihalomethyl, hydroxyl, nitro, cyano, alkoxy, alkyl, carboxyl, ester group.

[0065] "Aryl" refers to a group having at least one aromatic ring structure, i.e., an aromatic ring having a conjugated π electron system, including carbocyclic aromatic groups, heteroaryl groups, and biaryl groups. The aromatic group may be optionally substituted by one or more substituents selected from the following: halogen, trihalomethyl, hydroxyl, nitro, cyano, alkoxy, alkyl, carboxyl, ester group.

[0066] "Heteroaryl" refers to an aromatic group having 1 to 3 heteroatoms as ring atoms, the remaining ring atoms being carbon, and the heteroatoms include oxygen, sulfur and nitrogen. The ring may be a 5-membered or 6-membered ring. Examples of heterocyclic aromatic groups include furanyl, thienyl, pyridyl, pyrrolyl, N-alkylpyrrolyl, pyrimidyl, pyrazinyl, imidazolyl, etc. The heteroaryl group may be optionally substituted by one or more substituents selected from the group consisting of halogen, trihalomethyl, hydroxy, nitro, cyano, alkoxy, alkyl, carboxylic acid, and ester.

[0067] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0068] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0069] At present, battery electrodes are gradually turning to environmentally friendly and pollution-free water-based electrode systems, but the existing insulation coating formulation system is not suitable for water-based electrode systems. The reason is that the existing insulation coating formulation system is mostly an oily system, that is, N-methylpyrrolidone (NMP) is used as a solvent, and the binder used is mainly soluble in NMP, such as polyvinylidene fluoride (PVDF), polyimide, etc. Because NMP is a petroleum-derived chemical product, its synthesis and post-processing process are complicated, and when preparing the electrode, a large amount of NMP toxic gas will evaporate into the air, polluting the environment and causing harm to the human body, which is contrary to one of the main purposes of the water-based electrode system. Environmental protection. In addition, the above-mentioned oily formulation system of the insulation coating is incompatible with the water-based electrode. The solvent water in the water-based electrode system has different drying efficiencies from the solvent NMP in the existing insulation coating formulation system, resulting in poor drying of the electrode coating. During the continuous heating process, the film layer area is prone to over-drying, resulting in cracking, or even falling off.

[0070] Therefore, there is an urgent need for an aqueous insulating coating in the current aqueous electrode, which not only needs to have excellent adhesion but also needs to have water resistance to adapt to the application of aqueous batteries.

[0071] Based on this, the present application proposes to provide a water-based coating composition suitable for water-based electrodes, which comprises a water-based binder and a solvent. The water-based binder comprises a first polymer.

[0072] First polymer

[0073] The first polymer includes a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2).

[0074]

[0075] In formula (1), R1, R2, and R3 are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro, and L is a connecting bond or a C1-10 alkylene group.

[0076] The so-called C1-10 alkylene group refers to an alkylene group with 1 to 10 carbon atoms, for example, it may include but is not limited to methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene and decylene.

[0077]

[0078] In formula (2), R4, R5, and R6 are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro, and n=2 to 12.

[0079] The water-based binder in the present application has a special cross-linkable structure and carries a certain number of ester structures shown in formula (2), which changes the binder molecular chain from a linear structure to a more solid three-dimensional network structure, thereby improving the water resistance of the water-based coating. At the same time, the ester structure shown in formula (2) acts as a lipophilic group, which enables the water-based coating to better infiltrate and spread on the substrate (aluminum foil, etc.) to obtain a better bonding effect. As a result, the water-based membrane layer has high bonding strength and high water resistance, thereby improving the safety and cyclability of the battery.

[0080] In some embodiments, in formula (1), R1, R2, and R3 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano, L is a linking bond or a C3-4 alkylene group, and in formula (2), R4, R5, and R6 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano, and n=3-6, for example, 3, 4, 5, or 6. By making the above structural unit have the above functional group, the adhesion between the coating and the current collector can be further improved, and as the battery is used for a longer time, the improvement of the adhesion is conducive to further improving the cycle performance of the battery.

[0081] In some embodiments, in the first polymer, the mass proportion of the structural unit shown in the above formula (1) is 10% to 75%, and the value can be the end point value or any value between the end points, for example, it can be: 10%, 20%, 30%, 40%, 50%, 60%, 70%, 75%, but not limited to this. The mass proportion of the structural unit shown in the above formula (2) is 5% to 40%, and the value can be the end point value or any value between the end points, for example, it can be: 5%, 10%, 20%, 25%, 30%, 40%, but not limited to this. By making the mass proportion of the structural unit within the above range, a high-density cross-linked structure can be formed, which is beneficial to improve the water resistance of the water-based coating.

[0082] In some embodiments, the first polymer further comprises a structural unit represented by formula (3) and / or a structural unit represented by formula (4).

[0083]

[0084] In formula (3), R7, R8, and R9 are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro.

[0085] R 10 is a rigid group, optionally a cyano group, an acylamino group or an aryl group, optionally a cyano group.

[0086]

[0087] In formula (4), R 11 , R 12 , R 13 Each is independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxy, cyano or nitro, and m=2-12.

[0088] The structural unit shown in formula (3) is a hard segment that can provide strength to the material, and the structural unit shown in formula (4) is a soft segment that can provide flexibility to the material. This can enhance the wetting and spreading of the coating on the substrate, especially the oil-containing substrate (for example, oil-containing aluminum foil), which is beneficial to improving the adhesion and water resistance.

[0089] In some embodiments, in the first polymer, the mass percentage of the structural unit represented by the above formula (3) is 5% to 40%. The value may be an end point value or any value between the end points, for example, 10%, 20%, 30%, 40%, but not limited thereto. By making the content of the structural unit within the above range, it is more conducive to making the water-based coating have a moderate hardness and to improving the bonding force.

[0090] In some embodiments, in the first polymer, the mass proportion of the structural unit represented by the above formula (4) is 10% to 75%. The value can be an end point value or any value between the end points, for example, it can be: 10%, 15%, 20%, 30%, 40%, 50%, 60%, 70%, but it is not limited thereto. By making the content of the structural unit within the above range, it is more conducive to making the water-based coating have moderate flexibility and improving water resistance.

[0091] In some embodiments, in the first polymer, the mass proportion of the structural unit represented by the above formula (1) is 30% to 55%, the mass proportion of the structural unit represented by the above formula (2) is 5% to 15%, the mass proportion of the structural unit represented by the above formula (3) is 10% to 20%, and the mass proportion of the structural unit represented by the above formula (4) is 30% to 55%. By making the content of each structural unit within the above range, it is beneficial to form a three-dimensional network cross-linked structure, improve the adhesion of the water-based coating, and improve water resistance.

[0092] In some embodiments, the connecting bonds at both sides of each structural unit in the first polymer are connected to each other to form a polymer chain as shown below, but the connection method of each structural unit in the first polymer is not limited thereto.

[0093]

[0094] a and d are both any integer > 0, and b and c are both any integer ≥ 0. The values ​​of a, b, c and d may be the same or different.

[0095] In some embodiments, the number average molecular weight of the first polymer is 200,000 to 1,000,000, and optionally 300,000 to 600,000. By making the number average molecular weight within the above range, the binder molecular chains can be partially entangled inside the water-based coating, which is conducive to the formation of a three-dimensional network structure in the water-based coating and improves the bonding force. At the same time, by making the number average molecular weight within the above range, the above entanglement can be controlled within a moderate range, thereby obtaining excellent flexibility, thereby improving the water resistance of the water-based coating.

[0096] Second polymer

[0097] In some embodiments, the aqueous binder in the aqueous coating composition of the present application also includes a second polymer, which is different from the first polymer and contains a group that can react with the first polymer, and the above group can form hydrogen bonds and / or cross-linked structures with the first polymer. By further including the second polymer to form hydrogen bonds and / or cross-linked structures with the first polymer, a high-density three-dimensional network cross-linked structure can be formed, further improving the bonding force and further improving the water resistance of the aqueous coating. The so-called "the second polymer is different from the first polymer" includes: the various structural units of the second copolymer are different from the first copolymer; the various structural units of the second copolymer are the same as the first copolymer but the connection method of the various structural units is different; and the various structural units of the second copolymer are the same as the first copolymer but the mass proportion of each structural unit is different, etc.

[0098] In some embodiments, the second polymer comprises a flexible group, and the flexible group is a group comprising an ester bond or a group comprising an ether bond. The flexible group includes, but is not limited to, methyl acrylate, ethyl acrylate, propyl acrylate, methoxy, ethoxy, etc. The above groups can improve the flexibility of the coating, effectively reduce the risk of tab folding, help improve the water resistance of the coating, and improve the safety performance of the battery.

[0099] In some embodiments, the second polymer comprises a structural unit represented by formula (5), a structural unit represented by formula (6), and a structural unit represented by formula (7).

[0100]

[0101] In formula (5), R'1, R'2, and R'3 are the same as or different from R1, R2, and R3, respectively, and are independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro, and L' is the same as or different from L, and is a connecting bond or a C1-10 alkylene group. Here, the definition of "C1-10 alkylene group" is the same as that in the first polymer.

[0102]

[0103] In formula (6), R'4, R'5, and R'6 are the same as or different from R4, R5, and R6, respectively, and are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro, n' is the same as or different from n, and n'=2 to 12.

[0104]

[0105] In formula (7), R' 11 , R' 12 , R' 13 With R 11 , R 12 , R 13 are the same or different, and are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxy, cyano or nitro, m' is the same as or different from m, and m'=2-12.

[0106] The present application adopts a mixture of two polymers, wherein the carboxyl group of the structural unit represented by formula (1) and / or the hydroxyl group of the structural unit represented by formula (2) in the first polymer interacts with the carboxyl group of the structural unit represented by formula (5) and / or the hydroxyl group of the structural unit represented by formula (6) in the second polymer to form hydrogen bonds, or can further react with each other through treatments such as heating to form new chemical bonds such as ester bonds, thereby constructing a high-density three-dimensional network cross-linked structure inside the coating, thereby providing more sufficient adhesion for the water-based coating and further improving the water resistance of the water-based coating.

[0107] In addition, the structural unit represented by formula (3) in the first polymer, i.e., acrylonitrile monomer, is a hard monomer, which can provide strength to the material. The structural unit represented by formula (7) in the second polymer, i.e., acrylate monomer, is a soft monomer, which can provide flexibility to the coating. As lipophilic groups, they can better enable the water-based coating to infiltrate and spread on the substrate, especially the oil-containing substrate (e.g., oil-containing aluminum foil), which is beneficial to improve water resistance and improve battery safety.

[0108] In some embodiments, in formula (5), R'1, R'2, and R'3 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano, L' is a connecting bond or a C3-4 alkylene group, in formula (6), R'4, R'5, and R'6 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano, n'=3-6, in formula (7), R' 11 , R' 12 , R' 13 Each is independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl or cyano, and m'=3 to 6. Here, by making the above structural unit have the above functional group, the adhesion between the coating and the current collector is further improved, and as the battery is used for a longer time, the improvement of the adhesion is conducive to further improving the cycle performance.

[0109] In some embodiments, in the second polymer, the mass proportion of the structural unit represented by formula (5) is 10% to 60%, the mass proportion of the structural unit represented by formula (6) is 5% to 20%, and the mass proportion of the structural unit represented by formula (7) is 20% to 60%. By making the mass proportion of each structural unit within the above range, it is beneficial to form a high-density three-dimensional network system, which is beneficial to further improve the bonding force and further enhance the water resistance.

[0110] In some embodiments, the structural unit represented by formula (2) in the first polymer and the structural unit represented by formula (6) in the second polymer are both By using the structure of hydroxypropyl ester, that is, by controlling the length of the alkane chain, the swelling rate of the binder material in the electrolyte can be effectively reduced compared with the case of longer chains such as hydroxybutyl ester and hydroxyhexyl ester, so that the coating is effectively adhered to the substrate during long-term use, thereby further reducing the possibility of shedding. In addition, compared with the case of shorter chains such as hydroxymethyl ester and hydroxyethyl ester, because the carbon chain becomes longer, the pole piece coating is more flexible, reducing the risk of bending and brittle fracture of the coating, which is conducive to improving water resistance. In addition, by making the structural unit shown in formula (2) consistent with the structural unit shown in formula (6), the intermolecular force will be further enhanced, thereby improving the bonding force and improving water resistance.

[0111] In some embodiments, the structural units in the second polymer are connected to each other to form a polymer chain as shown below, but the connection method of the structural units in the second polymer is not limited thereto.

[0112]

[0113] Both e and g are any integer > 0, and f is any integer ≥ 0. The values ​​of e, f and g may be the same or different.

[0114] In some embodiments, the number average molecular weight of the second polymer is 200,000 to 1.2 million, and optionally 250,000 to 600,000. By making the number average molecular weight within the above range, the binder molecular chains can be partially entangled inside the water-based coating, which is conducive to the formation of a three-dimensional network structure in the water-based coating and improves the bonding force. At the same time, by making the number average molecular weight within the above range, the entanglement can be controlled within a moderate range, thereby obtaining excellent flexibility, thereby improving the water resistance of the water-based coating.

[0115] In some embodiments, the mass ratio of the first polymer to the second polymer is 9:1 to 1:9, or alternatively 4:1 to 1:4. By making the mass ratio of the first polymer to the second polymer within the above range, a high-density three-dimensional network system is formed, which is conducive to further improving the bonding force.

[0116] Water-based coating composition In some embodiments, the aqueous coating composition includes an insulating material and / or a dispersant in addition to the aqueous binder. Optionally, the insulating material is a ceramic material. Ceramic materials include but are not limited to aluminum oxide, boehmite, zirconium oxide, titanium oxide, silicon nitride, boron carbide, etc., and may be boehmite powder. As a dispersant, for example, a polyacrylamide-based dispersant may be used. In the coating, the carboxyl group of the structural unit shown in formula (1) in the first polymer and the carboxyl group of the structural unit shown in formula (5) in the second polymer can form hydrogen bonds with the insulating material boehmite, further improving the adhesion of the aqueous coating.

[0117] In some embodiments, water, such as deionized water, is used as a solvent. Compared with an oil-based electrode system using NMP as a solvent, using water as a solvent can reduce costs, achieve green environmental protection without pollution.

[0118] The water-based coating slurry may be prepared by the following method, but is not limited thereto.

[0119] (1) adding a dispersant to deionized water, and stirring the mixture for 5 min to 30 min at a dispersion speed of 500 rpm to 2000 rpm to obtain a dispersion (1);

[0120] (2) adding boehmite to the above dispersion (1), and dispersing and stirring for 30 min to 120 min at a dispersion speed of 500 rpm to 2000 rpm to obtain a dispersion (2);

[0121] (3) Add the first polymer as a binder to the above dispersion (2), and stir for 30 min to 120 min at a dispersion speed of 500 rpm to 2000 rpm to obtain a dispersion (3) as a water-based coating slurry.

[0122] When the water-based binder further comprises a second copolymer, the following steps are further performed:

[0123] (4) adding a second polymer as a binder to the above dispersion (3), stirring at a dispersion speed of 200 rpm to 1000 rpm for 15 min to 60 min to obtain a coating slurry; further, stirring at a dispersion speed of 500 to 800 rpm for 20 min to 40 min to obtain a water-based coating slurry.

[0124] Water electrode

[0125] The present application also provides an aqueous electrode, which includes an aqueous coating, wherein the aqueous coating is formed by the aqueous coating composition of the first aspect of the present application, and has a three-dimensional network cross-linked structure. By making the aqueous coating contain a three-dimensional network cross-linked structure, the water resistance of the aqueous coating is improved, and the risk of film peeling is reduced.

[0126] In some embodiments, the water-based coating contains 10% to 30% by mass of an aqueous binder relative to the total mass of the water-based coating, and optionally 15% to 25% by mass. By making the content of the binder within the above range, the bonding force of the water-based coating can be increased and the water resistance can be improved.

[0127] In some embodiments, the water-based coating contains 65% to 80% by mass of insulating material relative to the total mass of the water-based coating, and optionally 70% to 80% by mass. In addition, the water-based coating contains 0.2% to 1.0% by mass of dispersant relative to the total mass of the water-based coating, and optionally 0.5% to 0.8% by mass, thereby helping to improve the insulation effect.

[0128] In some embodiments, the contact angle between the above-mentioned aqueous coating and water is less than or equal to 90°, optionally 40° to 80°. The contact angle (θ) refers to the angle θ between the tangent line of the gas-liquid interface at the intersection of the gas, liquid and solid phases and the solid-liquid boundary line, which is a measure of the degree of wettability. If θ < 90°, the solid is lyophilic, that is, the liquid can wet the solid, and the smaller the angle, the better the wettability; if θ > 90°, the solid is lyophobic, that is, the liquid does not wet the solid, it is easy to move on the surface and cannot enter the pores.

[0129] In the present application, by making the contact angle between the aqueous coating and water within the above-mentioned range, the aqueous coating has good wettability in the aqueous electrode, the coating is more fully spread on the substrate, and the contact area is increased, which is beneficial to improving the adhesion of the aqueous coating to the surface of the substrate, improving the water resistance of the aqueous coating, and reducing the risk of falling off.

[0130] In some embodiments, the peel strength of the aqueous coating on the aqueous electrode is greater than or equal to 10 N / m, and optionally greater than or equal to 17 N / m. The peel strength can be obtained by performing a 180° peel test in accordance with the national standard GB / T 41511-2022.

[0131] In some embodiments, the aqueous electrode is an aqueous positive electrode or an aqueous negative electrode.

[0132] The aqueous coating composition of the present application can be used as an insulating coating in an aqueous positive electrode sheet. Figure 1 , the method for preparing the pole piece is explained by way of example.

[0133] In the preparation of the aqueous positive electrode of the battery, the insulating material, aqueous binder, dispersant, and deionized water can be made into aqueous coating slurry according to the above method, and the insulating coating slurry and the conductive layer slurry are respectively coated on at least one surface of the substrate 13 (aluminum foil), and then dried to form the insulating coating 12 and the conductive layer 11 on the substrate 13 to obtain the composite positive electrode current collector 1. Then, the slurry containing the active material is coated on the conductive layer 11 to form the active material layer 2, thereby making the pole piece.

[0134] During the drying process of the electrode sheet, under the action of heating, the carboxyl / hydroxyl groups in the water-based binder react to form hydrogen bonds and / or cross-linking structures, forming a three-dimensional network cross-linking structure. As a result, the resulting water-based electrode sheet has excellent bonding strength, improved water resistance, and can significantly reduce the occurrence of film peeling, thereby improving the safety performance of the battery.

[0135] The thickness of the single layer of the insulating coating formed by the water-based coating slurry is 1um to 20um, and optionally 2um to 8um. By making the thickness greater than 1um, a good insulating protection effect can be obtained, and by making the thickness less than 20um, it is beneficial to improve the battery energy density. In addition, the width of the insulating coating is 1mm-20mm, and optionally 3mm-10mm, thereby, it is beneficial to improve the battery energy density while obtaining a good insulating protection effect.

[0136] The surface density of the positive electrode film layer of the aqueous positive electrode plate of the present application is 250 mg / 1540.25 mm 2 ~500mg / 1540.25mm 2 , which can reach or even exceed the coating weight of oil-based electrodes. In addition, the drying temperature of water-based electrodes is 60℃-120℃, while the drying temperature of conventional oil-based electrodes is 110℃-140℃. Therefore, the application of water-based electrodes can greatly save energy consumption.

[0137] Aqueous battery

[0138] In one embodiment of the present application, an aqueous battery is provided.

[0139] The term "battery" referred to herein refers to a battery cell, a battery module or a battery pack.

[0140] Generally, a battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0141] [Positive electrode]

[0142] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the aqueous coating of the present application as an insulating coating.

[0143] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0144] In some embodiments, the positive electrode current collector is a composite current collector, which may include a substrate layer, and a conductive layer and an insulating layer disposed on at least one surface of the substrate layer.

[0145] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0146] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene polymer, and fluorine-containing acrylate resin.

[0147] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0148] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the aqueous positive electrode sheet, such as the positive electrode active material, the conductive agent, the aqueous binder and any other components are dispersed in a solvent (such as water) to form an aqueous positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0149] [Negative electrode]

[0150] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0151] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0152] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector includes a substrate layer and a conductive layer and an insulating layer disposed on at least one surface of the substrate layer.

[0153] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0154] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0155] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0156] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0157] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0158] [Electrolyte]

[0159] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The electrolyte includes electrolyte salt and solvent. The present application has no specific restrictions on the types of electrolyte salt and solvent, which can be selected according to needs.

[0160] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0161] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0162] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0163] [Isolation film]

[0164] In some embodiments, the aqueous battery further includes a separator. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0165] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0166] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0167] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0168] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0169] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square, or any other shape.

[0170] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0171] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0172] Electrical devices

[0173] In addition, the present application also provides an electrical device, the electrical device includes the battery provided in the present application. The battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0174] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0175] Example

[0176] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0177] Preparation Example

[0178] At 20°C, nitrogen was introduced into the reaction kettle for deoxygenation, and then 4.2 g of the surfactant sodium dodecylbenzene sulfonate was added to 90 g of deionized water, stirred and dissolved evenly, and then the monomers of formula (1) CH2=CHCOOH, the monomers of formula (2) CH2=CHCOO(CH2)3OH, the monomers of formula (3) CH2=CHCN, the monomers of formula (4) CH2=CHCOO(CH2)3CH3 and 0.05 g of the chain transfer agent n-dodecyl mercaptan were added in sequence and mixed evenly; then the temperature was raised to 85°C and stirred evenly to obtain a pre-emulsion.

[0179] Then, 1.5 g of initiator ammonium persulfate and 2.8 g of surfactant sodium dodecylbenzene sulfonate were continuously added dropwise to the pre-emulsion, and stirred at 300 rpm for 120 min to obtain a polymer seed solution. Then, 1.5 g of initiator ammonium persulfate was added, and stirring was continued at 300 rpm for 120 min to obtain a polymer.

[0180] Then, the polymer was post-treated, the temperature in the reactor was cooled to room temperature, and vacuum was maintained for 30 minutes before returning to normal pressure. Finally, the polymer was filtered with a 300-mesh filter, and the pH value was adjusted to 7-8 with lithium hydroxide to obtain a first polymer 1-20, the composition of which is shown in Table 1 below.

[0181] Referring to the above method, the first polymer and the second polymer in Table 1 and Table 2 were prepared according to the compositions shown in Table 1 and Table 2 below.

[0182] Table 1

[0183]

[0184]

[0185]

[0186] In the table, “-” means not added.

[0187] Table 2

[0188]

[0189] Example 1

[0190] (1) Preparation of water-based coating slurry

[0191] 91g of insulating material aluminum oxide, 2g of dispersant polyacrylamide (purchased from Dow Chemical, model 4045N, solid content 50%), and 16g of the first polymer 1-1 (solid content 50%) as an aqueous binder were added into deionized water to prepare an insulating coating slurry. The specific operation is as follows.

[0192] (1-1) adding a dispersant to deionized water, and stirring the mixture for 30 min at a dispersion speed of 1500 rpm to obtain a dispersion (1);

[0193] (1-2) adding aluminum oxide to the above dispersion (1), and stirring the dispersion at a dispersion speed of 1500 rpm for 60 minutes to obtain a dispersion (2);

[0194] (1-3) The first polymer 1-1 as a water-based binder is added to the above-mentioned dispersion (2), and stirred for 90 minutes at a dispersion speed of 1200 rpm to obtain a dispersion (3) as a water-based coating slurry.

[0195] When the water-based binder further comprises a second copolymer, the second polymer is added to the above dispersion (3), and stirred for 30 minutes at a dispersion speed of 800 rpm to obtain a water-based coating slurry.

[0196] (2) Preparation of current collector

[0197] Conductive graphite as a conductive material (purchased from Shanghai Kaiyin Chemical Co., Ltd., brand SP5000), dispersant xanthan gum (molecular weight of about 1000000 g / mol, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.), aqueous binder polyacrylic acid (number average molecular weight of 300000-800000), curing agent polycarbodiimide (number average molecular weight of 10000-40000) and water are prepared into a conductive slurry.

[0198] Then, the water-based coating slurry prepared in (1) is evenly coated on one surface of the positive electrode aluminum foil substrate, and coated in the edge area extending 10 mm from the edge of the substrate to the middle, and the above conductive slurry is evenly coated on the blank area of ​​the positive electrode aluminum foil substrate except the above edge area, with a coating speed of 50-150 m / min. After that, it is dried at 60°C-150°C. During the drying and heating process, the binder forms a three-dimensional network cross-linked structure in the water-based coating. Thus, a composite positive electrode current collector comprising a water-based coating (insulating layer) and a conductive layer is obtained, and the composition of the formed water-based coating is shown in Table 3.

[0199] (3) Preparation of aqueous positive electrode sheets

[0200] The positive electrode active material lithium iron phosphate, the conductive agent conductive carbon black, the dispersing stabilizer polyethylene and pyrrolidone, and the aqueous binder acrylic polymer are mixed in a solvent deionized water at a weight ratio of 96:1:1.2:1.8. After mixing evenly, an aqueous positive electrode slurry with a deionized water content of 40wt% and a solid content (solid content, including positive electrode active material, conductive agent, dispersing stabilizer and aqueous binder) of 60wt% is prepared. Then, the aqueous positive electrode slurry is evenly coated on the conductive layer of the composite positive electrode current collector prepared by the above (2), and dried to form an active material layer. After that, it is cold pressed and cut to obtain a positive electrode sheet.

[0201] (4) Preparation of negative electrode sheet

[0202] The negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) were dissolved in the solvent deionized water according to a weight ratio of 96.2:0.8:0.8:1.2, and after being mixed evenly, a negative electrode slurry with a deionized water content of 45wt% and a solid content (solid content, including negative electrode active material, conductive agent, binder and thickener) of 55wt% was prepared. Then, the negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet was obtained after drying, cold pressing, and slitting.

[0203] (5) Preparation of electrolyte

[0204] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 3 / 7, 12.5% ​​LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred evenly to obtain an electrolyte.

[0205] (6) Preparation of isolation membrane

[0206] A 7 μm thick PE porous film was used as a substrate, and then coated with a 2 μm thick ceramic coating, and the composite film was used as an isolation membrane.

[0207] (7) Preparation of lithium-ion batteries

[0208] The prepared aqueous positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a battery assembly. The battery assembly is placed in an aluminum shell and baked at 80°C to remove water, and then the electrolyte obtained in (5) is injected and sealed, and then a lithium-ion battery is obtained through processes such as standing, hot and cold pressing, formation, shaping, and capacity testing.

[0209] Example 2-36

[0210] The electrode was prepared in the same manner as in Example 1 so that the composition of the aqueous coating was as shown in Table 3, and then a battery was manufactured in the same manner as in Example 1.

[0211] In Table 3, "content (wt%)" refers to the content of water-based binder, insulating material and dispersant relative to the total mass of the water-based coating. "Boehmite" was purchased from Zhejiang Jidun New Material Technology Co., Ltd., Dv50 = 1.3 um.

[0212] Table 3

[0213]

[0214] In the table, “-” means not added.

[0215] Comparative Example 1

[0216] In the preparation of the coating slurry (1) of Example 1, boehmite (purchased from Zhejiang Jidun New Material Technology Co., Ltd., Dv50 1.3um) and binder PVDF (purchased from Solvay Chemical, model HSV900) were dispersed in the solvent NMP to prepare an insulating coating slurry with an NMP content of 88wt% and a solid content (including boehmite + binder) of 12wt%. In addition, the pole piece was prepared in the same manner as in Example 1, and then a battery was prepared.

[0217] Comparative Example 2

[0218] In the preparation of the coating slurry (1) of Example 1, only polyacrylic acid was used as a binder. Otherwise, a pole piece was prepared in the same manner as in Example 1, and then a battery was manufactured.

[0219] Comparative Example 3

[0220] In the preparation of the coating slurry (1) in Example 1, only polypropylene hydroxyethyl was used as a binder. Other than that, a pole piece was prepared in the same manner as in Example 1, and then a battery was manufactured.

[0221] The following tests were performed on the positive electrode sheets and batteries obtained in the above examples and comparative examples.

[0222] Pole coating inspection

[0223] According to the infrared spectrum analysis method of standard GB / T6040-2002, the water-based coating (insulating layer) of the positive electrode plate in the above embodiment is analyzed. The specific method is as follows:

[0224] The first polymers 1-1 to 1-20 were respectively used as test samples and put into IS10 Fourier transform infrared spectrometer produced by Nicolet Corporation of the United States for analysis.

[0225] In addition, the battery obtained in the example was disassembled to obtain a current collector including an aqueous coating (insulating layer), which was soaked in an electrolyte solvent diethyl carbonate (DEC) for 2 hours, and then the pole piece was washed 3 times with fresh DEC, and then dried to serve as a sample to be tested. Then, these samples to be tested were respectively placed in an IS10 Fourier transform infrared spectrometer of Nicolet Company of the United States for analysis.

[0226] The infrared spectra of the first polymers 1-1 to 1-20 were compared with the infrared spectra of the examples. In the infrared spectra of the examples, the carbonyl and carbon-oxygen single bond peaks were significantly red-shifted, proving that hydrogen bonds were formed in the water-based coatings of the examples.

[0227] Specifically, Figure 2This is an infrared spectrum diagram obtained by performing infrared testing on the first polymer 1-20. Figure 3 This is an infrared spectrum obtained by disassembling the battery prepared in Example 24 and conducting an infrared test on the aqueous coating of the positive electrode. Figure 2 and Figure 3 By comparison, the peak positions of carbonyl and carbon-oxygen single bonds are significantly red-shifted (1700.17 cm -1 →1732.33cm -1 and 1073.69cm -1 →1162.46cm -1 ), which shows that hydrogen bonds are formed in the water-based coating of Example 24 and a three-dimensional network cross-linked structure exists.

[0228] Pole performance test

[0229] (Immersion electrolyte performance test)

[0230] Take the electrode to be tested, the electrode has a good appearance. Use a blade to cut a sample with a width of 10mm and a length of 100mm, and immerse it in the electrolyte solvent made of EC\DMC\DEC with a compound ratio of 1:1:1. After immersing it at 60℃ for 24 hours, observe whether the coating falls off.

[0231] (Peel strength test)

[0232] Using a tensile testing machine, the 180° peel strength of the water-based coating was tested based on the national standard GB / T 41511-2022.

[0233] Take the electrode to be tested, the appearance of the electrode is good. Use a blade to cut a 10mm wide and 100-160mm long electrode sample. Stick the special double-sided tape NITTO.NO5000NS on the steel plate, the tape width is 10mm, and the length is 90-150mm. Stick the fixed-size electrode sample cut above on the double-sided tape, with the test surface facing down, and then use a 3kg roller to roll three times in the same direction on the surface of the positive electrode insulating coating. Insert a paper tape with a width equal to the electrode and a length greater than the sample length of 80-200mm under the electrode and fix it with wrinkled glue. The sample is then fixed on the testing machine. The end of the steel plate without the electrode is fixed with the lower clamp. The paper tape is folded upwards and fixed with the upper clamp. The axial direction of the electrode is consistent with the direction of force. The testing machine is loaded at a peeling speed of 10mm / min until the positive electrode breaks. The test is stopped and the maximum load force is recorded as F (unit N). The electrode width L = 20mm. According to f1 = F / L, the peel strength f1 (unit N / m) is calculated. The greater the peel strength, the higher the bonding strength.

[0234] (Water resistance test)

[0235] Take the electrode to be tested, the electrode has a good appearance. Use a blade to cut a 10mm wide and 100mm long electrode sample, and immerse it in a water-containing ultrasonic instrument. The ultrasonic instrument model is BRANSON CPX3800-HC, the ultrasonic frequency is 20KHZ, the ultrasonic power is 50W, and the stopwatch is turned on simultaneously to record the dissolution and shedding time of the water-based coating.

[0236] (Contact angle test)

[0237] With reference to the GB / T 30693-2014 standard document, the contact angle between the water-based coating (insulating layer) and water was tested, and deionized water was used as the liquid reagent.

[0238] Specifically, the current collector containing the aqueous coating to be tested is placed flat on the test platform, and then 0.6μL-1.0μL of deionized water is squeezed out through a microsyringe. The knob on the stage base is rotated to move the stage until it contacts the deionized water droplet, and the image is frozen within 10 seconds. The angle between the tangent of the outer surface of the droplet and the plane of the aqueous coating is measured by the angle measurement method as the contact angle.

[0239] Battery performance test

[0240] (Battery capacity retention rate test)

[0241] The battery capacity retention rate test process is as follows: at 25°C, the battery in the embodiment is charged to 3.65V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 3.65V, left for 5 minutes, and then discharged to 2.7V at 1 / 3C. The obtained capacity is recorded as the initial capacity C0. Repeat the above steps for the same battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time. The battery capacity retention rate Pn after each cycle is Cn / C0*100%. In this test process, the first cycle corresponds to n=1, the second cycle corresponds to n=2, ... the 100th cycle corresponds to n=100.

[0242] In the present application, the battery in the example was cycled 800 times under the above test conditions, and the capacity retention rate was calculated and shown in Table 4.

[0243] (Battery Vibration Abuse Test)

[0244] During the winding process of the battery assembly, the water-based coating (insulating coating) is folded in half and inserted about 2 mm on the innermost side of the battery assembly so that it contacts the active area of ​​the negative electrode plate, and the battery is obtained by the same method as the above-mentioned "Preparation of Lithium-ion Batteries".

[0245] The obtained battery is placed on a vibration table for 8 hours of vibration test in the three directions of X / Y / Z, and then the battery assembly is disassembled to confirm whether there is ablation at the crease of the pole piece. If ablation exists, it means that there is a short circuit inside the battery and the safety performance is poor. If there is no ablation, it means that the battery has good safety performance.

[0246] The test results of the above embodiments and comparative examples are shown in Table 4 below.

[0247] Table 4

[0248]

[0249] As shown in the data in Table 4, the aqueous coating of the positive electrode plates in Examples 1 to 36 of the present application has high adhesion and high water resistance. Specifically, the aqueous coating does not fall off after the positive electrode plates are immersed in the electrolyte, and the peel strength of the aqueous coating is greater than 8N / m, indicating that it has high adhesion. In the water resistance test, the coating fell off after a long time, and it has good water solubility. Moreover, the contact angles of the aqueous coating with water are less than 90°, indicating that the aqueous coating has good wettability, which is beneficial to improve the adhesion of the aqueous coating to the surface of the substrate. In addition, the aqueous batteries containing the aqueous coating of Examples 1 to 36 have a high capacity retention rate after 800 cycles, the battery has excellent cycle performance, and the battery has no ablation in the vibration abuse test, and the battery has good safety performance.

[0250] In the embodiments, compared with embodiments 1 to 21, embodiments 25 to 36 further contain a second polymer as an aqueous binder, and the first polymer and the second polymer form hydrogen bonds and / or cross-linking structures to form a high-density three-dimensional network cross-linking structure, and the adhesion and water resistance of the coating are further improved, thereby improving the cyclability and safety of the battery.

[0251] In Examples 30 to 36, the structural unit of formula (2) in the first polymer and the structural unit of formula (6) in the second polymer both include a specific structure (hydroxypropyl ester), thereby greatly improving the adhesion of the water-based coating, improving the water resistance, and enhancing the cyclability and safety of the battery.

[0252] In contrast, in Comparative Examples 1 to 3, the coating cannot take into account both high adhesion and high water resistance, the battery cycle performance is poor, and the battery safety is affected. Specifically, in Comparative Example 1, the oil-based coating slurry (binder PVDF + solvent NMP) is used in the water-based electrode. Although the oily coating shows high water resistance in the water resistance test, it is incompatible with the water-based electrode, the coating falls off, the adhesion is very poor, the cycle performance is poor, local ablation occurs, and the battery safety is poor. In Comparative Example 2, only polyacrylic acid is used as a binder, and in Comparative Example 3, only polypropylene hydroxyethyl is used as a binder. Since a three-dimensional network cross-linked structure is not formed in the coating, the water-based coating cannot obtain sufficient adhesion and water resistance, resulting in poor battery cycle performance and safety performance.

[0253] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A water-based coating composition, characterized in that: Contains water-based binder and solvent, The aqueous adhesive comprises a first polymer, wherein the first polymer comprises a structural unit represented by formula (1) and a structural unit represented by formula (2), In formula (1), R1, R2, and R3 are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro; L is a linking bond or a C1-10 alkylene group; In formula (2), R4, R5, and R6 are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro, and n=2 to 12.

2. The water-based coating composition according to claim 1, wherein In formula (1), R1, R2, and R3 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano; L is a connecting bond or a C3-4 alkylene group; In formula (2), R4, R5, and R6 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxy, or cyano, and n=3-6.

3. The water-based coating composition according to claim 1 or 2, wherein: In the first polymer, the mass proportion of the structural unit represented by the formula (1) is 10% to 75%, and the mass proportion of the structural unit represented by the formula (2) is 5% to 40%.

4. The water-based coating composition according to any one of claims 1 to 3, wherein The first polymer further comprises a structural unit represented by formula (3) and / or a structural unit represented by formula (4), In formula (3), R7, R8, and R9 are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano, or nitro. R 10 is a rigid group, optionally a cyano group, an acylamino group or an aryl group, optionally a cyano group, In formula (4), R 11 , R 12 , R 13 Each is independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxy, cyano or nitro, and m=2-12.

5. The water-based coating composition according to claim 4, wherein In the first polymer, the mass percentage of the structural unit represented by the formula (3) is 5% to 40%.

6. The water-based coating composition according to claim 4, wherein In the first polymer, the mass proportion of the structural unit represented by the formula (4) is 10% to 75%.

7. The water-based coating composition according to any one of claims 4 to 6, wherein In the first polymer, the mass proportion of the structural unit represented by formula (1) is 30% to 55%, the mass proportion of the structural unit represented by formula (2) is 5% to 15%, the mass proportion of the structural unit represented by formula (3) is 10% to 20%, and the mass proportion of the structural unit represented by formula (4) is 30% to 55%.

8. The water-based coating composition according to any one of claims 1 to 7, wherein The number average molecular weight of the first polymer is 200,000 to 1,000,000, and optionally 300,000 to 600,000.

9. The water-based coating composition according to any one of claims 1 to 8, wherein The aqueous binder further comprises a second polymer, which is different from the first polymer and comprises a group capable of reacting with the first polymer. The group is capable of forming a hydrogen bond and / or a cross-linked structure with the first polymer.

10. The water-based coating composition according to claim 9, wherein: The second polymer comprises a flexible group, Optionally, the flexible group is a group including an ester bond or a group including an ether bond.

11. The water-based coating composition according to claim 9 or 10, wherein: The second polymer comprises a structural unit represented by formula (5), a structural unit represented by formula (6) and a structural unit represented by formula (7), In formula (5), R'1, R'2, R'3 are the same as or different from R1, R2, R3, and are independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano or nitro; L' is the same as or different from L, and is a connecting bond or a C1-10 alkylene group; In formula (6), R'4, R'5, R'6 are the same as or different from R4, R5, R6, and are independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxyl, cyano or nitro, n' is the same as or different from n, and n'=2 to 12, In formula (7), R' 11 , R' 12 , R' 13 With R 11 , R 12 , R 13 are the same or different, and are each independently hydrogen, halogen, alkyl, hydroxyalkyl, alkoxy, cycloalkyl, alkenyl, alkynyl, heterocycloalkyl, aryl, heteroaryl, hydroxy, cyano or nitro, m' is the same as or different from m, and m'=2-12.

12. The water-based coating composition according to claim 11, wherein In formula (5), R'1, R'2, and R'3 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano, L' is a connecting bond or a C3-4 alkylene group, In formula (6), R'4, R'5, and R'6 are each independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxyl, or cyano, and n'=3 to 6. In formula (7), R' 11 , R' 12 , R' 13 Each is independently hydrogen, alkyl, hydroxyalkyl, alkoxy, hydroxy or cyano, and m'=3-6.

13. The water-based coating composition according to claim 11 or 12, wherein: In the second polymer, the mass proportion of the structural unit represented by formula (5) is 10% to 60%, the mass proportion of the structural unit represented by formula (6) is 5% to 20%, and the mass proportion of the structural unit represented by formula (7) is 20% to 60%.

14. The water-based coating composition according to any one of claims 11 to 13, wherein The structural unit of formula (2) is The structural unit of formula (6) is 15. The water-based coating composition according to any one of claims 9 to 14, wherein The number average molecular weight of the second polymer is 200,000 to 1.2 million, and optionally 250,000 to 600,000.

16. The water-based coating composition according to any one of claims 9 to 15, wherein The mass ratio of the first polymer to the second polymer is 9:1 to 1:9, and optionally 4:1 to 1:

4.

17. The water-based coating composition according to any one of claims 1 to 16, wherein The solvent is water.

18. The water-based coating composition according to any one of claims 1 to 17, wherein The composition further comprises an insulating material and / or a dispersant, Optionally, the insulating material is a ceramic material. Optionally, the ceramic material is boehmite powder. Optionally, the dispersant is a polyacrylamide-based dispersant.

19. A water-based electrode, characterized in that: Including water-based coatings, The water-based coating is formed from the water-based coating composition according to any one of claims 1 to 18 and has a three-dimensional network cross-linked structure.

20. The water-based electrode according to claim 19, wherein: The water-based coating layer contains 10% to 30% by mass of an aqueous binder relative to the total mass of the water-based coating layer, and optionally 15% to 25% by mass.

21. The water-based electrode according to claim 19 or 20, wherein: The water-based coating layer contains 65% to 80% by mass of an insulating material relative to the total mass of the water-based coating layer, and 0.2% to 1.0% by mass of a dispersant relative to the total mass of the water-based coating layer.

22. The water-based electrode according to any one of claims 19 to 21, wherein: The contact angle between the aqueous coating and water is less than or equal to 90°, and can be optionally 40° to 80°.

23. The water-based electrode according to any one of claims 19 to 22, wherein: The peel strength of the water-based coating in the water-based electrode is greater than or equal to 10 N / m, and optionally greater than or equal to 17 N / m. The peel strength is obtained by performing a peel test based on the national standard GB / T 41511-2022.

24. The water-based electrode according to any one of claims 19 to 23, wherein: The water-based electrode is a water-based positive electrode or a water-based negative electrode.

25. An aqueous battery, characterized in that: The invention comprises the water-based electrode according to any one of claims 19 to 24.

26. An electrical device, characterized in that: Includes the aqueous battery as described in claim 25.

Citation Information

Patent Citations

  • Binder for electrode composition for batteries

    JP2015144065A

  • Aqueous binder for electrode composition

    JP2015195114A

  • Binder for secondary battery electrode mixture layer, composition for secondary battery electrode mixture layer, and secondary battery electrode

    WO2020040148A1

  • Non-aqueous electrolyte secondary battery binder composition, electrode composition, electrode sheet, non-aqueous electrolyte secondary battery, production method for electrode sheet, and production method for secondary battery

    WO2021210603A1

  • Binder for secondary batteries, binder composition for secondary batteries, composition for electrodes, electrode sheet, secondary battery, method for producing electrode sheet, and method for producing secondary battery

    WO2022210737A1

Cited By

  • Aqueous coating composition, aqueous pole piece, and aqueous battery

    EP4667542A1